Усовершенствованные методы построения сейсмических изображений при картировании ловушек углеводородов, связанных с соляными куполами - Тяпкина, А.Н.; Тяпкин, Ю.К.; Окрепкий, А.И. (Геофизический журнал, 2014)
This paper is the first in a series of tutorials on the usage of modern migration methods for seismic imaging in areas of intense salt tectonics. In the paper, various types of hydrocarbon traps associated with salt domes in the Dnieper-Donets depression have been analyzed. Moreover, lassification of methods for seismic imaging has been given. With examples from other sedimentary basins, the benefits of pre-stack migration, a consideration of multipathing of seismic energy and the usage of converted waves in imaging of near stock objects have been shown. Запропонована стаття є першою у серії оглядових праць щодо використання сучасних методів міграції побудови сейсмічних зображень у районах з інтенсивною соляною тектонікою. Проаналізовано різноманітні типи пасток вуглеводнів, пов'язаних із соляними куполами у Ддіпровсько-Донецькій западині. Подано класифікацію методів побудови сейсмічних зображень. На прикладах з інших седиментаційних басейнів показано переваги міграції до підсумовування, урахування багатопроменевого поширення сейсмічної енергії та використання обмінних хвиль під час побудови зображень приштокових об'єктів.